PERBEDAAN MODEL PEMBELAJARAN OPEN INQUIRY DAN GUIDED INQUIRY BERDASARKAN KEMANDIRIAN BELAJAR DAN BERFIKIR TINGKAT TINGGI PADA MATA PELAJARAN BIOLOGI KELAS 11 MAN TEMPURSARI – NGAWI - Novita Adiqka Putri; Nurwidodo .; Yuni Pantiwati Pantiwati (University of Muhammadiyah Malang, 2015)
PERBEDAAN MODEL PEMBELAJARAN OPEN INQUIRY DAN GUIDED INQUIRY BERDASARKAN KEMANDIRIAN BELAJAR DAN BERFIKIR TINGKAT TINGGI PADA MATA PELAJARAN BIOLOGI KELAS 11 MAN TEMPURSARI – NGAWI Novita Adiqka Putri1, Nurwidodo1, Yuni Pantiwati 1 1Pendidikan Biologi FKIP Universtias Muhammadiyah Malang, e-mail : nurwidodo88@yahoo.com ABSTRACT Based on PISA (Programme for International Student Assessment) data which PISA is international studied about reading, math, and science literacy students achievement attained the age of 15 giving the result. In 2006 at Indonesia that students answer composition indicated lower understanding toward basic of science concepts (students could not interpret the data, explain casual relationship, solve the problems), limited expressing in mind, had lower scientific logical, lower ability toward basic of science concept and connection toward the surrounding facts. It is supported with lower teacher competency data and the usage of un-variation learning model. In that case, it is needed an learning model to solve the problem, one of learning model that can be used is Open Inquiry and Guided inquiry. In this present study, researcher used true-experiment by using simple random sampling technique. The purposes of this study are; (1) to know the differences study between Open Inquiry and Guided inquiry learning model, (2) to know the differences higher order thinking between Open Inquiry and Guided inquiry learning model. This research was hold in XI Science Class MAN TempursariNgawi. Independent Learningdata obtained based on temporary questionnaires, higher order thinking obtained by essay questions. The data analysis used by using one way Anova test. The result of this study showed that (1) Ftest>Ftable , 5.805 > 4.07till the using of learning model give different result toward independent learning, (2)Ftest>Ftable, 4.374 > 4.07till the using of learning model give different result toward higher order thinking skill. Key words: Inquiry, Open Inquiry, Guided inquiry, Independent Learning, Higher Order Thinking Skill.